2016
DOI: 10.1080/00028487.2016.1159614
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology of Dolphinfish in the Western Gulf of Mexico

Abstract: Dolphinfish Coryphaena hippurus support important commercial and recreational fisheries in the Gulf of Mexico. Understanding the feeding ecology of this economically important pelagic fish is key to its sustainable management; however, dietary data from this region are sparse. We conducted a comprehensive diet study to develop new trophic baselines and investigate potential ontogenetic and sex‐related shifts in Dolphinfish feeding ecology. The stomach contents of 357 Dolphinfish (27.6–148.5 cm TL) were visuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 50 publications
2
13
0
2
Order By: Relevance
“…being removed from an ecosystem, therefore play an important role in the trophic structure (Olson and Galván-Magaña, 2002;Varghese et al, 2013). Since this species is commonly associated with floating offshore objects, for example, fish aggregating devices or floating beds of Sargassum spp., it is an easy target for fisheries worldwide (Manooch et al, 1984;Massutí, et al, 1998;Rudershausen et al, 2010;Brewton et al, 2016). This study is the first to report on the largest macroplastic debris found in the stomach of the common dolphinfish, C. hippurus in the Southwest Atlantic Ocean.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…being removed from an ecosystem, therefore play an important role in the trophic structure (Olson and Galván-Magaña, 2002;Varghese et al, 2013). Since this species is commonly associated with floating offshore objects, for example, fish aggregating devices or floating beds of Sargassum spp., it is an easy target for fisheries worldwide (Manooch et al, 1984;Massutí, et al, 1998;Rudershausen et al, 2010;Brewton et al, 2016). This study is the first to report on the largest macroplastic debris found in the stomach of the common dolphinfish, C. hippurus in the Southwest Atlantic Ocean.…”
mentioning
confidence: 69%
“…Plastic debris has been reported worldwide in the stomachs of the common dolphinfish. For instance, pieces of plastic bags, a plastic bowl, pieces of rope, polyethylene sheets, wrappers, bottle caps, plastic ribbons, and even a badminton shuttlecock have been found in dolphinfish from the Pacific Ocean to the Indian Ocean (Manooch et al, 1983;Massutí et al, 1998;Vaske Junior and Lessa, 2004;Rudeershausen et al, 2010;Vanghese et al, 2013;Choy and Drazen, 2013;Brewton et al, 2016;Menezes et al, 2019). This large epipelagic species is known to be a voracious top predator, feeding on a wide range of pelagic and demersal organisms, including cephalopods, crustaceans, and several fish belonging to the Carangidae, Balistidae, Tetraodontidae, Exocoetidae, and Scombridae families (Massutí, et al, 1998;Carbonell et al, 1999;Varghese et al, 2013;Brewton et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Uma das hipóteses que pode suportar a presença dos quatro morfotipos está relacionada aos hábitos alimentares da espécie, i.e., um predador de topo com uma dieta baseada, predominantemente, no consumo de espécies epipelágicas com ampla ocorrência, associada à elevada produtividade na região -ressurgência de Cabo Frio (Valentin & Coutinho, 1990). Alguns autores têm reportado diferenças ontogenéticas e sazonais na dieta da espécie, estando tais variações associadas a distintos fatores (Oxenford & Hunte, 1999;Brewton et al, 2016), entre os quais se destaca a habilidade natatória da espécie, que permite a mesma explorar presas diversas em áreas distintas inclusive mais distantes da costa (Massutí et al, 1998). Além da alimentação outros atributos bionômicos, como o crescimento e a reprodução, também podem responder pelas conformações dos otólitos (Rossi-Wongtschowski, 2015).…”
Section: Discussionunclassified
“…Information on reproductive biology is an essential component in the study of the population dynamics and biology of any fish species (Hunter et al, 1992;Murua and Saborido-Rey, 2003). Several investigations were conducted to study the reproductive biology of C. hippurus from various parts of the world (Arocha et al, 1999;Castro et al, 1999;Wu et al, 2001;Zuniga-Flores et al, 2011;Furukawa et al, 2012;Santos et al, 2014;Gatt et al, 2015;Brewton et al, 2016). Despite the fact that C. hippurus is a commercially important fish contributing significantly to the Indian marine fishery, a detailed report on reproductive biology of C. hippurus is not available from the tropical Arabian Sea, except a few reports focusing on some aspects of reproductive biology (Rajesh et al, 2016;Vinod Kumar et al, 2017;Saroj et al, 2018).…”
Section: Introductionmentioning
confidence: 99%